Why does Everybody Hate me? Balance, Status, and Homophily: The Triumvirate of Signed Tie Formation - YAP, Janice (Institutional Knowledge at Singapore Management University, 2015)
Despite being one of the foundational theories of signed (positive/negative) tie formation, the evidence for balance theory is far from conclusive. A recent promising alternative is status theory, but a theoretical and explanatory gap still remains, with a dearth of theories and evidence. We put forward and test eight separate theories of signed tie formation on two face-to-face networks of friendship and esteem of 282 students. We use dimension reduction (factor analysis) on the results tables comparing the predictions of these eight theories for 50 ERGM parameters with our estimated models. We find three main paradigms explain the majority of signed network formation: balance, status, and homophily.